A practical method using a network of fixed infrared sensors for estimating crop canopy conductance and evaporation rate. (January 2018) - Jones, Hamlyn G.; Hutchinson, Paul A.; May, Tracey; Jamali, Hizbullah; Deery, David M.
Abstract : We describe the development and testing of a novel thermal infrared sensor incorporating a dry reference surface for incorporation into field wireless sensor networks (WSNs) that allows the estimation of absolute transpiration rates and canopy conductance. This 'dry reference' sensor provides a physical reference surface that mimics the temperature of a non-transpiring canopy and can therefore be used in conjunction with canopy temperature to estimate either canopy transpiration or canopy conductance. The dry reference sensor is based on a hemispherical surface that mimics the distribution of shaded and sunlit leaves in non-transpiring canopy. Three dry reference sensors were deployed in a commercial cotton crop from which canopy transpiration and conductance was estimated for the entire season. We provide evidence that fixed infrared sensors with a dry reference surface, when combined with limited meteorological data, can provide useful continuous monitoring of crop water use and canopy conductance that is potentially of value for irrigation management and crop phenotyping applications. Key to the success of this dry sensor application is the requirement that the spectral absorptance of the sensor is tailored to match the crop of interest. Highlights: A thermal sensor for crop Et and canopy conductance is described. The method depends on the use of artificial reference surfaces. A new type of reference surface is described. A wireless sensor network for the study of Et in different crops is described.